Analysis of Ozone Technology Interventions for Economic Recovery during the COVID 19 Pandemic: A Case Study of Batu Bara District through Chili Production Center - Nur, Muhammad; Baarri, Ahmad Ni’matullah Al; Sabrina, Tengku; Kusumiyati, Kusumiyati; Fauzi, Ahmad (Budapest International Research and Critics University, 2021)
The Center for Plasma Research (CPR), Diponegoro University, as the institution that drafted SNI 8759:2019, continues to oversee it implementation. In this paper, we report the successful implementation of SNI 8759:2019 at the chili center in Batu Bara. This success is strongly supported by the producer cooperative